Rediscovery of two species of Microlicia (Melastomataceae) in Minas Gerais, Brazil - Romero, Rosana; Woodgyer, Elizabeth M. (Phytotaxa, 2014)
Studies carried out in Minas Gerais state have led to the rediscovery of Microlicia maximowicziana and M. riedeliana, known previously only by the type collections made 190 years ago by LudwigRiedel. We present descriptions, commentson theaffinities among closelyrelatedspeciesandconservationassessments, as well as illustrations. Lectotypes for both species are designated and the varieties of M. maximowicziana are synonymised.